2021
DOI: 10.1177/1934578x211009692
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antioxidant, Antimicrobial and Potential Food Preserving Properties of Rubus Discolor (Rosaceae) Fruit Extracts

Abstract: The presented study was aimed at exploring the bioactive properties (antioxidant, antimicrobial and food preserving) and chemical composition of R. discolor fruits collected from 2 geographically distinct wild-growing populations and extracted by using different solvents (methanol, ethanol, acetone and water). The total phenol (TPC), flavonoid (TFC) and anthocyanin (TAC) content varied from 52.7 to 186.8 mg GAE/g, 3.5 to 7.0 mg QE/g and 11.1 to 28.2 mg/g dry weight (dw), respectively. HPLC-DAD analysis identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
4
1
Order By: Relevance
“…The acetone extracts exhibited the most promising activity, with IC 50 values of 120.3 and 258.4 μg/mL for Belgrado and Cer, respectively. However, these values are about five times higher than those found for the samples analyzed in the present study [ 47 ]. At the same time, the raspberry extracts investigated in this study exhibited a stronger ferric-reducing power than that found by Chwil et al [ 48 ], who investigated the antioxidant potential of the extracts from fruits of three cultivars, such as R. idaeus ‘Glen Ample’, ‘Laszka’, and ‘Radziejowa’ (cultivated in Poland); they found a reducing power similar to the cultivar R. idaeus ‘Heritage’, R. innominatus , and R. niveus , but it was lower than R. caucasicus × Chester , R. cyri , and R. insularis [ 49 , 50 ].…”
Section: Resultscontrasting
confidence: 86%
“…The acetone extracts exhibited the most promising activity, with IC 50 values of 120.3 and 258.4 μg/mL for Belgrado and Cer, respectively. However, these values are about five times higher than those found for the samples analyzed in the present study [ 47 ]. At the same time, the raspberry extracts investigated in this study exhibited a stronger ferric-reducing power than that found by Chwil et al [ 48 ], who investigated the antioxidant potential of the extracts from fruits of three cultivars, such as R. idaeus ‘Glen Ample’, ‘Laszka’, and ‘Radziejowa’ (cultivated in Poland); they found a reducing power similar to the cultivar R. idaeus ‘Heritage’, R. innominatus , and R. niveus , but it was lower than R. caucasicus × Chester , R. cyri , and R. insularis [ 49 , 50 ].…”
Section: Resultscontrasting
confidence: 86%
“…has been already described. In particular, the anti-listerial effect of ethanolic extract from R. discolor was demonstrated in vitro and in yoghurt by Veličković et al 11 , while the blackberry juice from R. fruticosus showed an inhibiting effect on L. monocytogenes , Salmonella Typhimurium and E. coli O157:H7 in milk and in BHI medium 15 .…”
Section: Resultsmentioning
confidence: 97%
“…Fruits, leaves, and young shoots of these species have been used in traditional medicine for several purposes 9 . Their phenolic extracts (PE) exhibit relevant antioxidant activity 10 , being rich in phenolic acids, flavonoids (anthocyanins, flavonols and tannins), carotenoids and organic acids 11 . Many of the molecules responsible for the antioxidant activity can inhibit the growth of microbial species.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between the chemical contents and antibacterial activity was studied by Pearson's correlation coefficients (r) using MANOVA. Values of r ≤ 0.35 represent weak correlation, r = 0.36 to 0.67 represent moderate correlation, and r = 0.68 to 1.0 represent strong correlation 11.…”
mentioning
confidence: 99%